2011
DOI: 10.1084/jem.20101854
|View full text |Cite
|
Sign up to set email alerts
|

Eph-B4 prevents venous adaptive remodeling in the adult arterial environment

Abstract: Stimulation of Eph-B4 prevents adaptive remodeling and preserves venous identity when veins are surgically placed into an arterial environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
86
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 55 publications
(96 citation statements)
references
References 50 publications
10
86
0
Order By: Relevance
“…24 Downstream regulators of Eph-B4 signaling in the endothelial cell include Akt, ERK1/2 25,26 and caveolin-1. 8 Our finding that eNOS is phosphorylated with stimulation of Eph-B4 in adult venous endothelial cells is consistent with previous reports that have shown that activation of Eph-B4 enhances NO production in endothelial cells in vitro. 8,25 We previously showed that reduced endothelial Eph-B4 signaling in endothelial cells derived from heterozygous Eph-B4 mice 27 was associated with diminished basal levels of eNOS protein expression and NO production but increased tube formation, 15 consistent with our data in vitro (Figure 3), but emphasizing the differences between endothelial cell function in vitro and in 3-dimensions, especially during vein graft adaptation in vivo.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…24 Downstream regulators of Eph-B4 signaling in the endothelial cell include Akt, ERK1/2 25,26 and caveolin-1. 8 Our finding that eNOS is phosphorylated with stimulation of Eph-B4 in adult venous endothelial cells is consistent with previous reports that have shown that activation of Eph-B4 enhances NO production in endothelial cells in vitro. 8,25 We previously showed that reduced endothelial Eph-B4 signaling in endothelial cells derived from heterozygous Eph-B4 mice 27 was associated with diminished basal levels of eNOS protein expression and NO production but increased tube formation, 15 consistent with our data in vitro (Figure 3), but emphasizing the differences between endothelial cell function in vitro and in 3-dimensions, especially during vein graft adaptation in vivo.…”
Section: Discussionsupporting
confidence: 93%
“…[19][20][21][22] We have previously shown that Eph-B4 expression is diminished during vein graft adaptation in adults, suggesting that successful vein graft adaptation, characterized by increased venous wall thickness and adaptive outward remodeling, is associated with loss of venous identity. 7,8 Our data also suggests that Eph-B4 is a negative regulator of eNOS during vein graft adaptation in vivo, with reduced Eph-B4 expression during vein graft adaptation associated with enhanced eNOS phosphorylation after 3 weeks (Figure 4), although not at 1 week postoperatively, 15 consistent with successful vein graft adaptation at 3 weeks in this model. Improving vein graft adaptation with increased NO production has led to the use of eNOS as a potential therapeutic agent.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…17 EphB4 heterozygous-knockout (EphB4+/−) EC were similarly isolated from EphB4+/− mice (The Jackson Laboratory). 5 Primary EC were immortalized by infection with retrovirus encoding the middle T antigen, and propagated in EBM2/EGM-2 MV SingleQuot Kit Supplement & Growth Factors (Lonza) supplemented with 15% fetal bovine serum (Hyclone), Penicillin-streptomycin, and L-glutamine in 5% CO 2 at 37°C. Culture media was changed every 2 days.…”
Section: Methodsmentioning
confidence: 99%
“…diminished EphB4 expression without induction of EphrinB2 expression. 45 EphB4, a member of the trans-membrane receptor tyrosine kinase family is a determinant of venous fate during embryonic development, whereas its ligand EphrinB2 is a determinant of arterial fate; interestingly, both EphB4 and EphrinB2 persist on adult veins and arteries, respectively. 67 Although the functions of EphB4 and EphrinB2 in adult cells are unknown, we have previously shown that EphB4 inhibits neointimal thickening of vein grafts, suggesting an active role for EphB4 in the limitation of venous wall thickness in adult veins.…”
mentioning
confidence: 99%